Party alignment, political budget cycles and vote within a federal country - Pablo Garofalo; Daniel Lema; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2016)
To understand how intergovernmental relations affect political budget cycles (PBCs) within federal countries, we model the credibility problems of discretionary fiscal policy in combination with a national incumbent that favors aligned districts. Analyzing Argentina's provinces during the 1985-2001 period, unsurprisingly, provincial budget balances worsen in electoral years, and aligned provinces (where the governor belongs to the president's party) receive larger federal transfers and have larger public expenditures during the governor's entire term. The main interaction effect in electoral years is that provincial budget balances only deteriorate in unaligned provinces, which receive less federal transfers. Furthermore, average federal transfers boost the vote for aligned governors. Two broad implications are that studies of subnational PBCs are biased by an omitted factor (discretional federal transfers), and that governors unaffiliated with the president suffer a "Cinderella" effect at the polls which helps the president dominate national politics.
Keywords: D72; E62; 330; federal countries; discretional transfers; party alignment; distributive politics; subnational political budget cycles